Burnout in Organizational Life - Halbesleben, Jonathon R.B.; Buckley, M. Ronald (Journal of Management, 2004)
Burnout is a psychological response to work stress that is characterized by emotional exhaustion, depersonalization, and reduced feelings of personal accomplishment. In this paper, we review the burnout literature from 1993 to present, identifying important trends that have characterized the literature. We focus our attention on theoretical models that explain the process of burnout, the measurement of burnout, means of reducing burnout, and directions for the future of burnout research.